Defining spatiotemporal characteristics of climate change trends from downscaled GCMs ensembles: how climate change reacts in Xinjiang, China. (25th January 2018) - Luo, Min; Liu, Tie; Frankl, Amaury; Duan, Yongchao; Meng, Fanhao; Bao, Anming; Kurban, Alishir; De Maeyer, Philippe
ABSTRACT: The fragile ecosystem, scarce water resources, and limited ecosystem resilience of Xinjiang, China make the region especially vulnerable to climate change. Researchers need reliable analyses of climate change trends to formulate regional mitigation and adaption strategies and to support sustainable development. Therefore, two statistical downscaling methods and the combination of a Mann–Kendall test with Co‐Kriging interpolation were used to investigate the spatiotemporal characteristics of climate change in Xinjiang based on the ensemble of 37 general circulation models (GCMs) in 2021–2060. The reliabilities of single run and ensemble downscaling results of GCMs were evaluated by 69 meteorological stations over the period 1965–2004. The correlation coefficients (CC) with the observations for precipitation and temperature ranged between 0.4–0.8 and 0.9–0.99 in the reference period, respectively. CC improved to 0.87 and was close to 1 after downscaling for precipitation and temperature, respectively. A pronounced increase of ca . 0.27–0.51 °C decade −1 was projected overall, and especially for Representative Concentration Pathway (RCP) 8.5 in northern Xinjiang. In general, the precipitation changed by −1.66 to 6.83% decade −1 while varying seasonally and spatially; a declining tendency emerged in the western regions of Xinjiang during summer. More extreme rainfall events are predicted to occur in summer and autumn months, while warmer extremes would be concentrated in August. The climate in Xinjiang will continue to become warmer and wetter. Nevertheless, Western Xinjiang will experience a warmer and drier climate in summer and autumn. These projections of climate change in the near future are able to provide useful information for the development of potential mitigation measures and adaptation strategies. Multiple circulation mechanisms are also suggested accounting for the changes in precipitation and temperature which will benefit the understanding of the possible drivers of climate variability in this region. Abstract : The location of Xinjiang Uygur Autonomous Region and meteorological stations used in this study. An inset map shows the location of Xinjiang within China.